2011
DOI: 10.1007/s00417-011-1897-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of corneal hysteresis and corneal resistance factor after corneal cross-linking for keratoconus

Abstract: ORA parameters demonstrate significant differences between KC and non-KC eyes. Both CH and CRF present significant correlations with visual acuity and corneal parameters. CXL exerts a non-significant impact on ORA measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 31 publications
6
39
0
4
Order By: Relevance
“…It has been repeatedly shown that crosslinking halts the progression of keratoconus, and the effects from corneal crosslinking have been convincingly demonstrated in vitro by biochemical (Spoerl et al 2004b;Brummer et al 2011), biomechanical (Wollensak et al 2003b;Knox Cartwright et al 2012;Dias et al 2013), structural (Wollensak et al 2004;Beckman Rehnman et al 2011) and thermomechanical (Spoerl et al 2004a) investigations. Demonstrating an increased biomechanical strength in vivo after CXL treatment using the Ocular Response Analyser (ORA), has been more difficult (Vinciguerra et al 2010;Spoerl et al 2011;Gkika et al 2012;Goldich et al 2012), but it is generally accepted today that CXL acts through an increase in corneal biomechanical strength (Beshtawi et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has been repeatedly shown that crosslinking halts the progression of keratoconus, and the effects from corneal crosslinking have been convincingly demonstrated in vitro by biochemical (Spoerl et al 2004b;Brummer et al 2011), biomechanical (Wollensak et al 2003b;Knox Cartwright et al 2012;Dias et al 2013), structural (Wollensak et al 2004;Beckman Rehnman et al 2011) and thermomechanical (Spoerl et al 2004a) investigations. Demonstrating an increased biomechanical strength in vivo after CXL treatment using the Ocular Response Analyser (ORA), has been more difficult (Vinciguerra et al 2010;Spoerl et al 2011;Gkika et al 2012;Goldich et al 2012), but it is generally accepted today that CXL acts through an increase in corneal biomechanical strength (Beshtawi et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This enables in vivo measurement of CH and the CRF [10]. In KCN corneas, CH and the CRF have been shown to be significantly decreased when compared with non-KCN corneas [11,22,23,24]. …”
Section: Corneal Biomechanical Propertiesmentioning
confidence: 99%
“…31 A number of publications, in which ORA was used, report on changes in ocular biomechanical properties in keratoconus eyes. 17,26,27,32,33 Statistically, CH and CRF are significantly lower in keratoconus eyes compared to normal eyes, but both parameters have low sensitivity and specificity for distinguishing between the groups, thus alone are not suitable for establishing the diagnosis. 32,33 Although CorVis ST analyses corneal deformations due to air puff applanation as well, parameters obtained by the two equipments cannot be compared.…”
Section: 811mentioning
confidence: 99%